Renal expression of Toll-like receptor 2 and 4: Dynamics in human allograft injury and comparison to rodents. Issue 1 (March 2015) - Stribos, Elisabeth G.D.; van Werkhoven, Maaike B.; Poppelaars, Felix; van Goor, Harry; Olinga, Peter; van Son, Willem J.; Damman, Jeffrey; Seelen, Marc A.
Highlights TLR2 and TLR4 expression dynamics in several human post-transplant injury biopsies. Unique opportunity to stain healthy human living donor biopsies for TLR2 and TLR4. Human acute rejection biopsies were characterized by TLR4+ infiltrating cells. A tubular staining was found in mouse and rat but not in human biopsies. Results from this study have an impact on future TLR inhibitor studies.